Phylogenetic relationship of Paramignya trimera and its relatives: an evidence for the wide sexual compatibility - Phi, Thi Cam Mien (Nature, 2022)
The genus Paramignya (Rutaceae) comprises about 30 species typically distributing in tropical Asia. Like other genera of the family Rutaceae, the significant variation in the morphology of Paramignya species makes the taxonomic study and accurate identification become difficult. In Vietnam, Paramignya species have been mostly found in Khanh Hoa and Lam Dong provinces and used as traditional medicines. Recently, Paramignya trimera, a species of the genus Paramignya with local name “Xao tam phan” has been drawn attention and intensively exploited to treat liver diseases and cancers. However, the significant variations in the morphology and different local names of P. trimera have caused confusion and difficulty in the accurate identification and application of this plant for medicine. In this study, the combination of both morphological and DNA sequence data has effectively supported the taxonomic identification of P. trimera and some relatives collected in Khanh Hoa and Lam Dong provinces. The comparison of the morphology and analysis of the phylogenetic trees suggested that there was a significant variation of P. trimera. In addition, some accessions of P. trimera with morphological characteristics similar and Atalantia buxifolia were likely the intergeneric hybrids between the two species. Analysis of genetic variation, interspecific and intraspecific distances using ITS, matK and rbcL sequences shown that P. trimera was closely related to A. buxifolia, Severinia monophylla and Luvunga scandens. In addition, matK sequences represented as the effective candidate DNA barcode to identify and distinguish Paramignya species from others of the family Rutaceae.